COMBINED ANTIMICROBIAL EFFECT OF THYMOL AND SODIUM LACTATE AGAINST LISTERIA MONOCYTOGENES AND SALMONELLA TYPHIMURIUM IN FISH PATTY - İlhak, Osman İrfan; Guran, Husnu Sahan (My University, 2014)
The purpose of this study was to evaluate the antimicrobial efficacy of the combinations of thymol (0.1 w/w) and sodium lactate (1 and 2% v/w) against Listeria monocytogenes and Salmonella Typhimurium in fish patty samples stored at 4C for 5 days. Treatment with the combination of 0.1% thymol + 2% sodium lactate did not show a significant inhibition on the L. monocytogenes when compared with the sample treated with 2% sodium lactate alone. However, treatment of fish patty with the combination of 0.1% thymol + 2% sodium lactate showed a synergistic effect on Salmonella Typhimurium on days 3 and 5 of storage.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: THYMOL; SODIUM LACTATE; LISTERIA MONOCYTOGENES; SALMONELLA TYPHIMURIUM; FISH PATTY